Editors' Introduction - Cunningham, Philip A.; Gregerman, Adam; Joslyn-Siemiatkoski, Daniel; Langer, Ruth (Studies in Christian-Jewish Relations, 2026)
This is the Editors' Introduction for the multiyear international research project entitled “Jesus the Jew / Jesus the Christ: Explorations of His Jewish Identity and Its Meanings.”